Kad Hari Raya - Tai, Lin Lin; -, Lisa; Chow, P. C.; Kok, P. A.; Loke, John; Diong, Jimmy
Kad ucapan hari raya yang diutuskan kepada Profesor Diraja Ungku Abdul Aziz daripada warga Hoon Thai Sdn. Bhd Tai Lin Lin, Lisa, P. C. Chow, P. A. Kok, John Loke, Jimmy Diong